The Functional Consequences of Relative Substrate Specificity in Complex Biochemical Systems - Zeng, Yan (Frontiers in Genetics, 2011)
A biochemical activity, that is, enzymatic reaction or molecular interaction, frequently involves a molecule, for example, an enzyme, capable of interacting with numerous substrates or partners. Specificity is a fundamental property of biochemical activities, and relative specificity refers to the situation whereby a molecule interacts with multiple substrates or partners but with different affinities. Here, a hypothesis is proposed that any molecule, such as an enzyme, would have a range of preferences or relative specificity for its many native substrates, which differentially impacts the phenotypes of these substrates and hence shapes the relevant biological processes in vivo. While the mechanisms underlying the specific recognition between enzymes and individual substrates have been studied extensively, whether any enzyme exhibits intrinsic selectivity towards its ensemble of substrates is often overlooked, and whether this selectivity has any functional consequences is much less appreciated. There are, however, several lines of evidence in the literature that are consistent with the hypothesis and reviewed here. Furthermore, this hypothesis is supported by our analyses of a number of diverse biochemical systems at a large scale. Thus, the human microRNA processing machinery possesses relative specificity towards its hundreds of substrates, which might contribute to differential microRNA biogenesis; the promoter binding affinity of the transcription factor Ndt80 might regulate Ndt80 target mRNA expression in the budding yeast; Cdk1 kinase specificity might lead to variable substrate phosphorylation in vivo; and the density of HuR deposition to its thousands of RNA targets might partly explain differential RNA expression in human cells. It is proposed, therefore, that relative specificity is a universal property of complex biochemical systems and that the hypothesis could denote a general principle in biology.